Concentration and velocity measurement of flowing objects using optical and ultrasonic tomography - Saad, Mohd. Sazli (2007)
This thesis investigates a simple measurement of concentration and velocity of objects flowing in a pipe of 100mm diameter. The project aims to analyze the accuracy and repeatability of measurements by comparing the results from the concentration and velocity measurement of various objects between optical and ultrasonic sensors. Both sensors are based on process tomography technique. The optical and ultrasonic tomography measurements circuit consists of sensors, signal conditioning circuits and data acquisition system. Sensors fixture are designed based on fan beam projection technique. The signal is transmitted from the transmitter to the receiver. Interfacing card is used to interface the analog signals to the computer. The sensors detect the attenuation of light for optical system and acoustic energy for ultrasonic system. This provides information on the concentration of the flowing objects. To measure velocity, two arrays of sensors are placed upstream and downstream on the pipe. The output from both sensors is cross-correlated. The peak of the cross-correlation graph represented the time for the object to move from upstream to downstream. The velocity is obtained by dividing the time and the distance between upstream and downstream. The velocity is obtained by simply dividing the time and the distance between upstream and downstream. Prototype circuits have been implemented for optical and ultrasonic measurement system. Visual Basic 6.0 is used for software algorithms on concentration and velocity measurement. The data is collected using data acquisition system and it was an offline process. The comparison of concentration profiles has shown that optical tomography produced a better result compared to ultrasonic tomography. Whereas for velocity measurement, ultrasonic transducer produced better accuracy but lower repeatability compared to optical transducer.